Three-component reaction of N-isocyaniminotriphenylphosphorane (Ph3PNNC), biacetyl, and a carboxylic acid in water. (3rd March 2016) - Jafari, Ali; Ramazani, Ali; Ahankar, Hamideh; Asiabi, Pegah Azimzadeh; Sadri, Fariba; Joo, Sang Woo
GRAPHICAL ABSTRACT: ABSTRACT: Reaction of N -isocyaniminotriphenylphosphorane with biacetyl in the presence of a carboxylic acid in water proceeds smoothly at RT (20–26°C) and neutral conditions to afford sterically congested 1, 3, 4-oxadiazole derivatives in high yields. The reaction proceeds smoothly and clearly under mild conditions and no side reactions were observed.